2011
DOI: 10.5194/angeo-29-1939-2011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Arctic tides at CANDAC-PEARL (80° N, 86° W) and Svalbard (78° N, 16° E) for 2006–2009: radar observations and comparisons with the model CMAM-DAS

Abstract: Abstract. Operation of a Meteor Radar (MWR) at EuThe three-year monthly means for both diurnal (DT) and semi-diurnal (SDT) winds demonstrate significantly different amplitudes and phases at Eureka and Svalbard. Typically the summer-maximizing DT is much larger (∼24 m s −1 at 97 km) at Eureka, while the Svalbard tide (5-24 m s −1 at 97 km)) is almost linear (north-south) rather than circular. Interannual variations are smallest in the summer and autumn months. The High Arctic SDT has maxima centred on August/Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Figure demonstrates that during days 280–310, the SW1 component is actually the strongest contribution to the observed 12‐hr variability at these latitudes, and during springtime (between approximately days 80 and 140) the three zonal components are of a similar amplitude. By comparing radar data from Svalbard (78°N, 18°E) and the CANDAC‐PEARL station (80°N, 86°W), Manson et al () observed a weak, but significant, SW1 SDT which was strongest around March–June, together with a mix of SW1 and SW3 SDTs in late autumn/winter in addition to the dominant migrating (SW2) SDT. This is in good agreement with the results presented here from slightly lower latitudes and also with the TIDI satellite results of Iimura et al () from around 60°N discussed earlier.…”
Section: Climatology Of the Superdarn Sdtsmentioning
confidence: 99%
“…Figure demonstrates that during days 280–310, the SW1 component is actually the strongest contribution to the observed 12‐hr variability at these latitudes, and during springtime (between approximately days 80 and 140) the three zonal components are of a similar amplitude. By comparing radar data from Svalbard (78°N, 18°E) and the CANDAC‐PEARL station (80°N, 86°W), Manson et al () observed a weak, but significant, SW1 SDT which was strongest around March–June, together with a mix of SW1 and SW3 SDTs in late autumn/winter in addition to the dominant migrating (SW2) SDT. This is in good agreement with the results presented here from slightly lower latitudes and also with the TIDI satellite results of Iimura et al () from around 60°N discussed earlier.…”
Section: Climatology Of the Superdarn Sdtsmentioning
confidence: 99%
“…Given the pitfalls in temperature estimation above [ Dyrud et al , 2001] and below [ Ballinger et al , 2008] 90 km, we feel that our “safe” approach of “sticking to” 90 km is justified. It is unfortunate we find this necessary, because 90 km is the assumed altitude of the summer mesopause at 78°N [ Höffner and Lübken , 2007] (although see the modeling results reported by Manson et al [2011a, 2011b]) and by examining altitudes between 80 and 100 km with NSMR one could search for trends both above and below the summer mesopause, and for that matter in a 20 km deep regime of the winter mesosphere.…”
Section: Physical Processesmentioning
confidence: 99%